Towards a Cloud Service Broker for the Meta-Cloud - Gonçalves, Carlos (2015)
Cloud Computing provides computing resources, middleware and (web-based) software on an on-demand basis.This model helps customers saving costs and allows access to the latest technology. With the exponential growth of IT companies offering cloud services, deploying applications to the cloud has become a complex task to engage. Almost each and every provider has its own terminology, providers do not share the same (or even similar) API, and costs of operation greatly diverge according to provider, region or availability.This paper propounds a Cloud Service Broker (CSB), anddescribes an early prototype, where users are, intelligently and autonomously, aid to deploy, manage, monitor and migrate their applications in a cloud of clouds. A single API is required to orchestrate the whole process in tandem with two truly decoupled managers: a Platform as a Service Manager (PaaS Manager) and an Infrastructure as Service Manager (Iaas Manager). Users also interact with the CSB through a Web portal and a command-line interface.